Survival after lymphadenectomy of nodal metastases from melanoma of unknown primary site. Issue 1 (28th February 2023) - Gullestad, Hans Petter; Ryder, Truls; Goscinski, Mariusz
Abstract: Although the vast majority of melanomas have a primary site, 3%–4% of all melanomas in distant sites display no known primary site (MUP). This phenomenon is not fully understood and various hypotheses have been introduced. The prognostic significance of MUP has been unclear, with some studies showing no survival benefit while others find improved survival compared to stage-matched patients with melanoma of known primary site (MKP). Between 1997 and 2014, 864 patients underwent an en bloc resection of clinical nodal metastases at a referral centre for metastatic melanoma in Norway. The MUP ( n = 113) and MKP ( n = 751) patients were graded with stage III or IV. The overall survival (OS) was calculated with the Kaplan-Meier method, and multivariate analysis identified factors of significance for the two groups. A significant five-year OS emerged for stage III, MUP = 58% and 42% for MKP, but not for stage IV. The five-year relapse-free survival (RFS) was 41% and 31% for MUP and MKP respectively ( p = 0.049). The statistically significant inter-group differences (MUP/MKP) were observed in the univariate and multivariate analyses of age, gender, number of affected nodes, tumour size and perinodal growth within stage III and tumour size within stage IV. After regional lymphadenectomy, MUP patients with clinical nodal metastases had a better outcome than MKP patients. This finding supports the theory that an endogenously mediated immune response may promote the regression of a cutaneous melanoma.